Tracking the Ionospheric Response to the Solar Eclipse of November 03, 2013. (22nd October 2014) - Amabayo, Emirant Bertillas; Anguma, Simon Katrini; Jurua, Edward
Abstract : The ionospheric dynamics is highly influenced by the solar radiation. During a solar eclipse, the moon occults the solar radiation from reaching the ionosphere, which may drastically affect the variability of the ionosphere. The variability of total electron content (TEC) observed by dual frequency Global Positioning System (GPS) receivers has made it possible to study effects of solar eclipse on the ionosphere. Total eclipse occurred on November 03, 2013, and the maximum amplitude was visible at Owiny in northern Uganda. Ionospheric behavior during this eclipse was analysed by using TEC data archived at Mbarara (MBAR), Malindi (MAL2), Eldoret (MOIU), and Kigali University (NURK) International GPS Satellite (IGS) stations. TEC variations of four consecutive days were used to study instantaneous changes of TEC during the eclipse event. The results generally show TEC decrease at the four stations. However, a maximum perturbation amplitude of ≥20 TECU was observed at MAL2 (18:00–20:00 UT) which is further south of the equator than the other stations. TEC enhancement and depletion were observed during the totality of the eclipse at MOIU, MBAR, NURK, and MAL2 (13:00–15:00 UT). This study found out that the ionospheric TEC over East Africa was modified by wave-like energy and momentum transport and obscuration of the solar disc due to the total solar eclipse.